2016
DOI: 10.1097/cad.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of taurine on doxorubicin-induced acute hepatotoxicity through suppression of oxidative stress and apoptotic responses

Abstract: The organ toxicity of doxorubicin (DOX), an anthracycline antineoplastic agent, narrows the therapeutic window despite its clinical usefulness. In the present study, we determined whether taurine protected against DOX-induced hepatic injury, and explored the molecular mechanisms underlying the suppressive effects of taurine in terms of alterations in oxidative stress and apoptotic responses. DOX-induced body weight loss was completely suppressed by taurine treatment. Elevations in the serum activity levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…In the present study, the decrease in GSH after DOX administration was suppressed by concurrent theanine treatment, but the SOD activity was not significantly altered by DOX. In light of the findings of our previous study [22], the change in the GSH levels in the kidneys of DOX-treated rats was minor compared with that in the liver. This may be attributed to the existence of potent defense systems to eliminate ROS in the kidneys, but DOX was clearly shown to impair the renal functions by increasing oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the decrease in GSH after DOX administration was suppressed by concurrent theanine treatment, but the SOD activity was not significantly altered by DOX. In light of the findings of our previous study [22], the change in the GSH levels in the kidneys of DOX-treated rats was minor compared with that in the liver. This may be attributed to the existence of potent defense systems to eliminate ROS in the kidneys, but DOX was clearly shown to impair the renal functions by increasing oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…Taurine, a mammalian amino acid, was shown to protect neurons from glutamate cytotoxicity, maintain MMP, and reduce ROS in SH-SY5Y cells [222]. Taurine also protected mitochondria by activating Akt-CREB-peroxisome proliferator-activated receptor gamma co-activator 1-α (PGC1α) pathway [223,224,225]. In prenatally-stressed (PS) rats that had defects in learning and memory, taurine reduced mitochondrial ROS, restored MMP, COX, ATP, and SOD2, and increased Akt-CREB signaling pathway and PGC1α expression in the hippocampi [223].…”
Section: Natural Compounds That Can Activate Nrf2 And/or Neurotropmentioning
confidence: 99%
“…However, DOX causes various toxic effects, the most common of which is cardiotoxicity (2). Multiple mechanisms are involved in DOX-induced cardiomyopathy, including the increase in cardiac oxidative stress, as evidenced by reactive oxygen species that induce damage such as lipid peroxidation, and changes in adenylate cyclase activity leading to apoptosis and inflammation-related signaling pathways (3,4). It has previously been suggested that DOX also elicits inflammatory effects by increasing the expression levels of nuclear factor kappa-B (NF-κB), and induces the production of various proinflammatory mediators, including tumor necrosis factor (TNF)-α (5).…”
Section: Introductionmentioning
confidence: 99%